Peningkatan Pemahaman Terkait Muatan Barang Berbahaya (Dangerous Goods) dan Blind Spot di SMAN 7 Denpasar - Baskara, Wahyu Padma; Nengah Widiangga; Novianto, Hendra Yuda; Sofiana, Resza Ajie Okta; Raharjo, Agung Slamet (LOSARI DIGITAL, 2023)
It is important to understand about dangerous goods and the procedures for transporting dangerous goods, especially for the younger generation. This can help reducing the number of accidents in the transportation of goods to help the transport of dangerous goods. Based on this, the Bali Land Transportation Polytechnic provides insight about lind spots for dangerous goods transportation. This activity uses socialization/counseling methods regarding the load of dangerous goods on the road and blind spots. The target of this program is students of SMAN 7 Denpasar, because there is a close relationship between role of students and driving safety regarding to dangerous goods transportation. this socialization hopefully provides an understanding of dangerous goods and the role of the younger generation in transportation safety. During this socialization, participants can understand the explanation and answer the questions correctly